2016
DOI: 10.3233/jad-160513
|View full text |Cite
|
Sign up to set email alerts
|

Serum SHBG Levels are not Associated with Longitudinal Cognitive Decline in Mild Cognitive Impairment

Abstract: SHBG levels did not influence the rate of cognitive decline in MCI. Further studies to confirm these findings and uncover other potential mechanisms of gender differences in the risk for AD may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…Despite serum SHBG levels being often elevated in females [19,23], we did not observe such changes in CSF, which may indicate that sex related SHBG differences might be more pronounced in blood than in CSF [16]. The lack of association of CSF SHBG with CSF YKL-40 or p/tTau ratio suggests that SHBG is not related to neuroinflammatory processes or Tau proteostasis.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Despite serum SHBG levels being often elevated in females [19,23], we did not observe such changes in CSF, which may indicate that sex related SHBG differences might be more pronounced in blood than in CSF [16]. The lack of association of CSF SHBG with CSF YKL-40 or p/tTau ratio suggests that SHBG is not related to neuroinflammatory processes or Tau proteostasis.…”
Section: Discussioncontrasting
confidence: 74%
“…Interestingly, such association was likely driven by the FTLD-Tau, which showed a correlation coefficient considerably stronger than the FTLD-TDP group (−0.38 vs. −0.02). Previous studies have shown that not only SHBG but also other hormones (e.g., estrogen, free thyroxin or thyroidstimulating hormone) are associated with MMSE [22,23], suggesting that changes in the whole hypothalamic-pituitary (HP) axes may influence memory function and the risk of dementia or AD [24,25]. This is supported by different neuropathological and imaging studies, highlighting the importance of HP dysfunction (e.g., body weight, circadian rhythm, sleep) in AD pathophysiology [25].…”
Section: Discussionmentioning
confidence: 99%
“…In older men, with increasing age, the level of SHBG increases. Additionally, compared with healthy aging males, the level of SHBG in elderly AD patients increased significantly (27). However, levels of SHBG have no relationship with cognitive decline in patients with cognitive impairment according to the Alzheimer's Disease Assessment Scale-Cognitive section (28).…”
Section: Relationship Between Decreased Androgens and Impaired Cognitmentioning
confidence: 86%
“…A longitudinal cohort study consisting of 514 women and 217 men over 65 years of age found that per SD increase in serum SHBG levels was associated with a 20–30% increased risk for incident dementia with a mean of 5.2 years follow-up [17]. In contrast, findings from the Alzheimer’s Disease Neuroimaging Initiative-1 study involving 371 elderly adults (including 134 women) with mild cognitive impairment reported no significant association between serum SHBG levels and the rate of cognitive decline during 8-year follow-up [18]. The limited sample size, the heterogeneity of participants, or different inclusion criteria in these studies may result in the discrepancy across studies.…”
Section: Discussionmentioning
confidence: 99%